Investigation of topography of the surface and distribution of mechanical properties usingScanning Nanoindenter "NanoScan" of the Ca-P coatings deposited on medical implants by the high-frequency magnetron sputtering technique; 9th International Conference on Modification of Materials with Particle Beams and Plasma Flows, Tomsk, 21-21September 2008 - Kozelskaya A. I. Anna Ivanovna; Surmenev R. A. Roman Anatolievich; Tverdokhlebov S. I. Sergei Ivanovich; Useinov S.; Pichugin V. F. Vladimir Fyodorovich
The paper presents the results of investigation of topography of the surface and distributionof mechanical properties of the thin biocompatible Ca-P coatings. Hydroxyapatite (HA) thinfilms were prepared by the rf-magnetron sputtering technique. The depositions were performed from pure HA target on Si and glassceramic substrates. The procedure of the deposition was following: working gas - Argon, power of radio-frequency generator - 290 W, frequency ν = 5.28 MHz. The topography measurements and the measurement of maps of surface mechanical properties at the same surface area, hardness measurements (indentation and sclerometry tests) and elastic modulus measurements (using the unique spectroscopy technique)of the HA coatings were investigated by Scanning Nanoindenter “NanoScan”. The thicknessof the coatings was from 0.8 to 3 μm. An average surface roughness of coatings was 12-13 class